A Proposed Model to Behaviourally Pricing Risk - Peeperkorn, Jacques (Journal of Economics and Behavioral Studies, 2014)
To imagine that asset pricing is not dependant on behavioural heuristics and game theory, we are required to reduce the definition of the participants to that of utility maximising, risk-averse, uniform automata. This study examines this statement through an application of behavioural theory that speaks to the ability of investors to perceive risk, as well as the interactive effects of game theory to distort the perception of risk from exogenous variables to that of endogenous probability beliefs. We present a foundation for a state-space model, such as a Kalman filter, to be used in pricing risk.